My world the essential guide to Kion's world - Last, Shari (New York, New York DK Publishing, 2017)
"Meet Prince Kion! Discover Kion's world and learn all about being leader of the Lion Guard. Use the stickers to help Kion protect the Pride Lands!"--
"More than 100 fun stickers"--Front cover
Comic stories
1
Keywords: Toy and movable books -- Specimens; Toy and movable books; Animals -- Africa -- Fiction; Lion -- Fiction